Identification of key genes responsible for green and white colored spathes in Anthurium andraeanum (Hort.) - Li, Jieni; Tan, Quanya; Yi, Maosheng; Yu, Zhengnan; Xia, Qing; Zheng, Lu; Chen, Jianjun; Zhou, Xiaoyun; Zhang, Xiang-Qian; Guo, He-Rong (Frontiers in Plant Science, 2023)
Modern anthuriums, Anthurium andraeanum (Hort.) are among the most popular flowering plants and widely used for interior decoration. Their popularity is largely attributed to the exotic spathes with different colors. Previous studies have reported color development in red spathe cultivars, but limited information is available on key genes regulating white and green colored spathes. This study analyzed anthocyanin, chlorophyll, and carotenoid contents as well as transcript differences in spathes of eight cultivars that differed in spathe colors ranging from red to white and green. Results showed that increased expression of a transcription factor AaMYB2 was associated with elevated levels of anthocyanin in spathes, but decreased expression of AaMYB2 and increased expression of AaLAR (leucoanthocyanidin reductase) and AaANR (anthocyanidin reductase) were accompanied with the accumulation of colorless proanthocyanidin, thus the white spathe. As to the green colored spathe, chlorophyll content in the green spathe cultivar was substantially higher than the other cultivars. Correspondingly, transcripts of chlorophyll biosynthesis-related genes AaHemB (porphobilinogen synthase) and AaPor (protochlorophyllide oxidoreductase) were highly upregulated but almost undetectable in white and red spathes. The increased expression of AaHemB and AaPor was correlated with the expression of transcription factor AaMYB124. Subsequently, qRT-PCR analysis confirmed their expression levels in nine additional cultivars with red, white, and green spathes. A working model for the formation of white and green spathes was proposed. White colored spathes are likely due to the decreased expression of AaMYB2 which results in increased expression of AaLAR and AaANR, and the green spathes are attributed to AaMYB124 enhanced expression of AaHemB and AaPor. Further research is warranted to test this working model.